2023
DOI: 10.3390/nu15092083
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Dietary Sugars and Glycaemic Index with Indices of Glucose Metabolism and Body Fatness during 3-Year Weight Loss Maintenance: A PREVIEW Sub-Study

Abstract: Background: Dietary sugars are often linked to the development of overweight and type 2 diabetes (T2D) but inconsistencies remain. Objective: We investigated associations of added, free, and total sugars, and glycaemic index (GI) with indices of glucose metabolism (IGM) and indices of body fatness (IBF) during a 3-year weight loss maintenance intervention. Design: The PREVIEW (PREVention of diabetes through lifestyle Intervention and population studies in Europe and around the World) study was a randomised con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…High GI foods rapidly increased glucose level after a meal compared to low GI foods [16] [19] [20]. Many studies had demonstrated that intake of low GI diet can not only improve glycemic control but also provide benefits with prevention of diabetes and coronary heart disease [21] [22] D. Khanna et Food and Nutrition Sciences [23].…”
Section: Introductionmentioning
confidence: 99%
“…High GI foods rapidly increased glucose level after a meal compared to low GI foods [16] [19] [20]. Many studies had demonstrated that intake of low GI diet can not only improve glycemic control but also provide benefits with prevention of diabetes and coronary heart disease [21] [22] D. Khanna et Food and Nutrition Sciences [23].…”
Section: Introductionmentioning
confidence: 99%